2014
DOI: 10.1007/s10803-014-2096-8
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Corpus Callosum Connectivity, Socio-communicative Deficits, and Motor Deficits in Children with Autism Spectrum Disorder: A Diffusion Tensor Imaging Study

Abstract: In addition to social and communicative deficits, many studies have reported motor deficits in autism spectrum disorder (ASD). This study investigated the macro and microstructural properties of the corpus callosum (CC) of 18 children with ASD and 12 typically developing controls using diffusion tensor imaging tractography. We aimed to explore whether abnormalities of the CC were related to motor deficits, as well as social and communication deficits in children with ASD. The ASD group displayed abnormal macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…With appropriate scaling, the corpus callosum in ASD was found to be smaller and the volume of the corpus callosum did not proportionately increase with overall cerebral cortex volume. Decrease in volume and size of the corpus callosum has been replicated in other MRI and imaging technology studies, as well (Thomas et al 2011;Prigge et al 2013;Hanaie et al 2014). The reduced volume of the corpus callosum as a whole, not regionally, in ASD has also been found in autistic adolescents and adults (Egaas et al 1995;Gardener et al 2011).…”
Section: White Matter Abnormalities -Callosal Pathwaysmentioning
confidence: 57%
See 1 more Smart Citation
“…With appropriate scaling, the corpus callosum in ASD was found to be smaller and the volume of the corpus callosum did not proportionately increase with overall cerebral cortex volume. Decrease in volume and size of the corpus callosum has been replicated in other MRI and imaging technology studies, as well (Thomas et al 2011;Prigge et al 2013;Hanaie et al 2014). The reduced volume of the corpus callosum as a whole, not regionally, in ASD has also been found in autistic adolescents and adults (Egaas et al 1995;Gardener et al 2011).…”
Section: White Matter Abnormalities -Callosal Pathwaysmentioning
confidence: 57%
“…; Hanaie et al. ). The reduced volume of the corpus callosum as a whole, not regionally, in ASD has also been found in autistic adolescents and adults (Egaas et al.…”
Section: Discussionmentioning
confidence: 98%
“…Also noteworthy is that structural alterations of corpus callosum are one of the most consistent neuroanatomical findings in autism. However, previous sMRI studies in autistic individuals demonstrated no association between corpus callosum and motor impairment [Hanaie et al, ; Mengotti et al, ]. Taken together, NSS‐related WM variations in the corpus callosum may be similar, but perhaps less severe than those in patients with neurodevelopmental disorders, still suggesting a common pathomechanism.…”
Section: Discussionmentioning
confidence: 81%
“…In other words, no studies to date have reported higher microstructural (functional anisotropy (FA), mean diffusivity (MD), radial diffusivity (RD), axial diffusivity (AD)) or macrostructural (tract volume) properties in individuals with autism compared to TD controls (but see Ray, Miller, Karalunas, Robertson, Grayson et al, 2014). In contrast, the most consistent finding in these studies is reduced microstructural properties of the white matter tracts and volume of the corpus callosum (Hanaie, Mohri, Kagitani-Shimono, Tachibana, Matsuzaki et al, 2014;Schaer et al, 2013;Shukla et al, 2011;Travers, Tromp, Adluru, Lange, Destiche et al, 2015). Other converging structural connectivity findings include reduced microstructural properties of the inferior fronto-occipital fasciculus (IFOF) and the inferior longitudinal fasciculus (ILF) (Koldewyn et al, 2014) in individuals with autism, which are two long-range fiber tracts that originate within the occipital lobe and traverse the temporal lobe, with the ILF terminating in the anterior temporal lobe and the IFOF terminating in the frontal lobe.…”
Section: Structural Connectivitymentioning
confidence: 99%